THE USE OF AUDIO-VISUAL IN TEACHING SOCIOLINGUISTICS: CODE-SWITCHING OR CODE-MIXING - maria ramasari (EDUCAFL : Journal of Education of English as Foreign Language, 2018)
ABSTRACT This research aimed to investigate and describe the finding about the use of movie in teaching sociolinguistics: code-switching or code-mixing. This research applied qualitative research using descriptive method. In collecting the data, the researcher used observation, interview and documentation. Based on the result of data analysis, it could be concluded that the use of audio-visual in teaching sociolinguistics: code-switching or code-mixing showed good response of the students’ attention and participation in Sociolinguistics class. Key words: Audio-visual, teaching sociolinguistics: code-switching or code-mixing